Answer:
x = (i sqrt(7))/4 - 3/4 or x = -(i sqrt(7))/4 - 3/4
Explanation:
Solve for x:
x - 1 - 2/x = 3 x + 2
Bring x - 1 - 2/x together using the common denominator x:
(x^2 - x - 2)/x = 3 x + 2
Multiply both sides by x:
x^2 - x - 2 = x (3 x + 2)
Expand out terms of the right hand side:
x^2 - x - 2 = 3 x^2 + 2 x
Subtract 3 x^2 + 2 x from both sides:
-2 x^2 - 3 x - 2 = 0
Divide both sides by -2:
x^2 + (3 x)/2 + 1 = 0
Subtract 1 from both sides:
x^2 + (3 x)/2 = -1
Add 9/16 to both sides:
x^2 + (3 x)/2 + 9/16 = -7/16
Write the left hand side as a square:
(x + 3/4)^2 = -7/16
Take the square root of both sides:
x + 3/4 = (i sqrt(7))/4 or x + 3/4 = -(i sqrt(7))/4
Subtract 3/4 from both sides:
x = (i sqrt(7))/4 - 3/4 or x + 3/4 = -(i sqrt(7))/4
Subtract 3/4 from both sides:
Answer: x = (i sqrt(7))/4 - 3/4 or x = -(i sqrt(7))/4 - 3/4